The Islamization Of Human Resource Management TEXTBOOK FOR HIGHER EDUCATION IN INDONESIA THROUGH AL-FARUQI’S THEORY - Wiryanto, Wisber (UIN Ar-Raniry, 2016)
The Western secularization is a main cause of educational problems and extremely damaging if it is not solved immediately. Based on al Faruqi’s theory, the only way to solve educational problems caused by secularization of Human Resource Management (HRM) is through the Islamization of Knowledge (IOK). The research used descriptive qualitative method will answer a main question: how is the operationalization of Al Faruqi’s theory solving education problem caused by the secularization? This research aims to apply the IOK al-Faruqi theory into the IOHRM concept, with the framework consists of the input through 15 HRM textbooks, which are used by several universities in Indonesia with Western worldview as a dominant tendency than Islamic worldview. This research analysis the process and synthesis of Western and Islamic-legacy of HRM; and as its output, a non-secular HRM textbook using Islamic worldview approach. As the result, this output will reduce the dominance of the secular HRM textbook in Western worldview approach. The findings of this research are: (1) To create the IOHRM concept derived from the IOK al-Faruqi theory, which is applied through a process of analysis and synthesis of Western and Islamic-legacy of HRM; (2) Analysis of the IOHRM, through the process analyzes the category, and then analyze the relevance, differences and problems of Western and Islamic-legacy of HRM; (3) Synthesis of the IOHRM, by integrating Western and Islamic-legacy of HRM, using the dual process of the IOK al-Attas theory in Islamic worldview approach; and (4) an Islamic HRM textbook.